Long-term follow-up of surgical intervention pattern in pediatric low-grade gliomas: report from the German SIOP-LGG 2004 cohort - Thomale, Ulrich-Wilhelm; Gnekow, Astrid K.; Kandels, Daniela; Bison, Brigitte; Driever, Pablo Hernáiz; Witt, Olaf; Pietsch, Torsten; Koch, Arend; Capper, David; Kortmann, Rolf-Dieter; Timmermann, Beate; Harrabi, Semi B.; et al. (Journal of neurosurgery. Pediatrics, 2022)
OBJECTIVE Neurosurgical treatment is an integral part of the treatment algorithms for pediatric low-grade glioma (LGG), yet patterns of surgical procedures are rarely challenged. The objective of this study was to evaluate surgical treatment patterns in pediatric LGG. METHODS The German Societé Internationale d’Oncologie Pédiatrique (SIOP)-LGG 2004 cohort was analyzed to identify relevant patient and tumor characteristics associated with time to death, next surgery, number of resections, and radiological outcome. RESULTS A total of 1271 patients underwent 1713 neurosurgical interventions (1 intervention in 947, 2 in 230, 3 in 70, and 4-6 in 24). The median age of the study population was 8.57 years at first surgery, and 46.1% were female. Neurofibromatosis type 1 (NF1) was found in 4.4%, and 5.4% had tumor dissemination. Three hundred fifty-four patients (27.9%) had chemotherapy and/or radiotherapy. The cumulative incidence of second surgery at 10 years was 26%, and was higher for infants, those with spinal and supratentorial midline (SML) tumors, and those with pilomyxoid astrocytomas. The hazard ratio for subsequent surgery was higher given dissemination and noncomplete initial resection, and lower for caudal brainstem and SML tumors. Among 1225 patients with fully documented surgical records and radiological outcome, 613 reached complete remission during the observation period, and 50 patients died. Patients with pilocytic astrocytoma had higher chances for a final complete remission, whereas patients with initial partial or subtotal tumor resection, dissemination, NF1, or primary tumor sites in the spinal cord and SML had lower chances. CONCLUSIONS Neurosurgery is a key element of pediatric LGG treatment. In almost 50% of the patients, however, at least some tumor burden will remain during long-term follow-up. This study found that most of these patients reached a stable disease status without further surgeries. Multidisciplinary team decisions must balance the goal of complete resection, risk factors, repeated surgeries, and possible treatment alternatives in a wide range of heterogeneous entities. Procedural details and neurological outcome should be recorded to better assess their impact on long-term outcome.
Publication date: 22 July 2022
Gesehen am 18.01.23